Analisis Komparatif Praktik Gadai Lahan dalam Perspektif Mazhab Abu Hanifah dan Syafi‘i - Fahrudin, Ahmad; Muhajir; Ma’rufi, Anwar (Kartika: Jurnal Studi Keislaman, 2025)
This qualitative-comparative case study aims to analyze and compare the traditional practice of land pawn (rahn) in Padureso Village, Kebumen, from the perspective of Islamic jurisprudence (fiqh) according to the Imam Abu Hanifah and Imam Syafi'i Schools of Thought (Madzhabs). This study is relevant as it highlights the unique customary aspects concerning the utilization of the pledged object (marhun). Primary field data indicate a deviation in practice, where the pledged land is entirely managed and utilized by the creditor (murtahin), who also takes all the produce without any revenue sharing with the landowner (rahin), despite receiving permission for use. The analysis reveals fundamental differences in the juristic views. The Imam Abu Hanifah Madzhab generally prohibits the murtahin from benefiting from the marhun as it is deemed potential usury (riba), even with the rahin's permission. Conversely, the Imam Syafi'i Madzhab tends to prohibit utilization by the murtahin if it is stipulated in the contract (akad), but may permit it if there is genuine consent from the rahin outside the contract. Therefore, the practice in Padureso Village, which grants full profit to the murtahin, is categorized as a void pledge (rahn fasid) because it contains an element of usury or violates the essential nature of the collateral contract.